Consciousness and modern culture the emerging new culture [videorecording]. (Spectrum Foundation, 1987)
Summary: Discussion of the new holistic culture that emerged in the late twentieth century. Capra argues that the biological sciences, quantum physics and systems theory will provide a theoritical foundation which will supersede the decaying culture based on a linear, mechanistic worldview.